2021
DOI: 10.4103/njm.njm_104_21
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Salivary Immunoglobulin a and Immunoglobulin G in Type 2 Diabetic Patients

Abstract: Background: Diabetes mellitus is a chronic disorder of glucose metabolism and it is associated with a compromised oral immunity. Salivary immunoglobulins offer a comprehensive protection for the oral cavity; however, there is insufficient data regarding their levels in type 2 diabetic patients. This study aimed to measure salivary Immunoglobulin G (IgG) and Immunoglobulin A (IgA) in diabetic patients in comparison to healthy nondiabetic controls. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The age group of the children involved, and the presence of caries and other periodontal diseases may have constituted important confounders. It is however noteworthy that other studies showed that certain salivary proteins like immunoglobulins, defensins and cathelicidin are reportedly overexpressed in the oral cavity of patients with diabetes although they still do not protect them, and the mechanism behind this finding are not clear [ 19 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age group of the children involved, and the presence of caries and other periodontal diseases may have constituted important confounders. It is however noteworthy that other studies showed that certain salivary proteins like immunoglobulins, defensins and cathelicidin are reportedly overexpressed in the oral cavity of patients with diabetes although they still do not protect them, and the mechanism behind this finding are not clear [ 19 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oral cavity is estimated to be harbouring over 400 different species of bacteria but their pathogenicity is curtailed by the immunological cells and antimicrobial proteins within the saliva which baths the cavity [ 16 ]. More than 300 proteins have been isolated from the saliva; only a few of those proteins have antimicrobial activities [ 17 - 19 ]. Being the first line of protection against invading microbes, the innate antimicrobial proteins in the saliva are critical in maintaining the integrity of the oral cavity.…”
Section: Introductionmentioning
confidence: 99%